Experimental investigation of natural convection heat transfer characteristics in MWCNT-thermal oil nanofluid - Ilyas, S.U. (2019)
The carbon nanotubes are considered as one of the highest thermal conductive material which is having a variety of heat transfer applications. The suitability of carbon nanotubes in convective heat transfer is examined using multi-wall carbon nanotubes (MWCNT)-thermal oil-based nanofluids. Stable nanofluids are prepared in the concentration range of 0â1Â mass and Prandtl number range of 415 â¤ Pr â¤ 600 using ultrasonication. The natural convection heat transfer behavior is studied experimentally in a vertical rectangular enclosure with aspect ratio 4. The heat transfer experiments are conducted at varying heat flux in the range of 1594â3150Â WÂ m â2 . The heat transfer coefficient, Nusselt number and Rayleigh number are estimated for MWCNT-thermal oil-based nanofluids and are compared with pure thermal oil. A significant deterioration in heat transfer coefficient is observed at higher concentrations of nanofluids. The study signifies the adverse impact on the cooling performance of MWCNT-thermal oil-based nanofluids in natural convection heat transfer, even though higher thermal conductivities are observed in nanofluids. It is found that not only thermal conductivity is essential property in heat transfer, but other thermophysical properties are also influential towards thermal management. Â© 2018, AkadÃ©miai KiadÃ³, Budapest, Hungary.